Persepsi Guru Mata Pelajaran Bahasa Indonesia Terhadap Pembelajaran Sastra Indonesia Dalam Kurikulum 2013 Di SMP Kab. Pacitan - Pandudinata, Reza (2016)
The purpose of this research are presented: (1) the teacher's perception of Indonesian Language subjects regarding the proportion of Indonesia's literary learning material, (2) the excess of Indonesia literature, learning, and (3) learning barriers the literature Curriculum in Indonesia to 2013 in junior high. This type of research i.e. qualitative descriptive study. Data collection techniques are used i.e. quisioner or question form and continued the interview. The validity of the data in this study using triangular triangular or source data. Technique of data analysis performed i.e. interactive analysis. The results of this study are: (1) the majority of teachers agree that the proportion of literary material with material language is around 20%: 80%. (2) the advantages of learning literature includes four aspects, namely (a) the material, i.e. material at least spur teachers to be more creative, material already adjust the reality of real life, easy to understand, the book provides the complete package of materials, and to develop students ' creativity. (b) from the media for example, when the full school media, makes it easy for teachers in teaching, the media adjust the development in the new era, the worksheet is already available in the student book packs, media utilization of highly preferred. (c) aspects of the method, the current method more flexible services, and methods able to make literature more interesting. (d) the process of learning, the learning process is very interest literature students, and if a good enough teacher mastery of material, then the learning process also goes well. (3) the obstacles come from some aspects of which (a) the material such as the lack of literary material, the material is very boring because it discussed repeatedly, the various types of text that the newly conceived too many teachers, and administration. (b) from the media as the difference in the ability of the school in complete media-media learning, some teachers feel no barriers. (c) From the side of the method, the teachers are still in the stage of searching the right methods, interpretation of literature needs to be improved. the purpose of learning literature adjusted again. (d) Lastly, from the learning process, namely the limited allocation of time, the culture of reading and writing literature that is still low, the study of literature less attractive, the assignment is not related to the matter, the assessment process is quite complex, the limitations of understanding and knowledge of the students, the learning process is implemented and adapted to the interests, policies, teachings, and weak if rowdy in a State of learning. Keywords: perception of teachers, Indonesian Language, learning literature, curriculum of 2013.